INCREASING SOCIAL DEVELOPMENT OF CHILDREN AGED 5-6 YEARS THROUGH TRADITIONAL MAKASSAR GAMES SONGKOK-SONGKOK JANGANG (International Conference on Social and Islamic Studies, 2021)
The purpose of this study is to demonstrate an improvement in the social development of children aged 5-6 years through traditional Makassar Songkoksongkok Jangang games at Nurul Falah Kindergarten in Bontomarannu Village, District Bontotiro, Bulukumba Regency. This study employs a quantitative approach to quasi-experimental research, with a one-group pretest-posttest design. The sample size was 12 children aged 5-6 years. The study's instrument was an observation sheet, which was analyzed using non-parametric statistics and the Wilcoxon-signed ranking test. The p-value of 0.002 indicated that there was a difference in the average value of children's social development before and after playing the traditional Makassar Songkok-songkok Jangang game (p 0.05). This is demonstrated by an increase in the average score before (28.75) to the average value of children's social development after (50.17) playing the traditional Makassar Songkok-songkok Jangang in Nurul Falah Kindergarten, Bontomarannu Village, district. Bontotiro, Bulukumba Regency. An increase in the social development of children aged 5-6 years through traditional Makassar games, songkok-songkok, does not imply that teachers or parents of children will continue to traditionalize traditional games in children and develop them to meet the needs of the times.